Migrações induzidas por fatores climáticos na América do SuL: os acordos sobre residência dos cidadãos do Mercosul e associados como forma de reconhecimento e integração - Granado, Karina (2020)
The general aim of this thesis was to investigate the existence of consolidated norms in MERCOSUR to be adapted to the migrants induced by climatic factors as implementation of the process of integration phase of the free movement of people and as a way of recognition and permanent assistance. To achieve the central aim, specific objectives were carried out for the reflexive conduction of the proposed theoretical and factual interweaving: (i) to establish ranges and conceptual and motivating differences between migration, refuge and displacement; (ii) to determine the relationship between environmental impacts (whether progressive or sudden) arising from climate change and migration statistics in South America; (iii) to analyze the academic research scenario on the relationship between the climate crisis and human displacement in South America; (iv) to define, based on the Theory of Legal Integration in the context of South America, what were the innovations brought by the MERCOSUR Residence Agreements and to analyze the (non)existence of other institutional forms coordinated and produced by the experiences of this integration process; and (V) to establish the possibility of integrating the multilateral mechanisms existing in MERCOSUR, based on the Residence Agreements, and to examine a possible granting of (temporary) humanitarian visas overcoming, enabling permanent assistance. Methodologically, in order to achieve these objectives, this applied research was revealed (according to CERVO; BERVIAN, 2002; GIL, 2010; LAKATOS; MARCONI, 2017), as it proposes the production of knowledge for application in specific situations, such as protecting the current legal vulnerability of environmental displacements in South America starting from the MERCOSUR Residence Agreements. This is also an exploratory study since from greater familiarity with the problem, it proposes to make the issue more explicit through further in-depth of ideas and concepts, and an explanatory research, by identifying the factors that contribute to the occurrence of certain phenomena, such as the case of climatic factors motivating a large number of human displacements (GIL, 2010). It is also classified as Bibliographic Research and as Documentary Research because books, scientific articles, theses, dissertations, periodical publications such as online newspapers and academic journals were used as bibliographic sources on technical procedures (CERVO; BERVIAN, 2002). As for the results and discussions, it started from the hypothesis of recognizing the MERCOSUR Residence Agreements as valid instruments for the application of a process of recognition and protection of environmental migration and displacement by disasters, which was confirmed in the sense of this application being revealed as a quick measure in the face of environmental emergencies and, consequently, migratory emergencies that are on the horizon. In this sense, waiting for multilateral negotiations and discussions in order to normatively establish a new migratory category and underlying documents, and only then being possible to receive these groups, would be to make waiting perpetrate human rights violations, even though there are immediately sufficient and capable Residence Agreements to start receiving migrations induced by climatic factors. Thus, it was noticed that the Residence Agreements have an initial support aspect, and it is from them that the migratory theme is built in MERCOSUR. Hence, it was found, in terms of research conclusions, that there are no specific regulations capable of regulating the transit and reception in the receiving countries regarding environmental migration and those who travel through environmental disasters across MERCOSUR borders. Therefore, the Residence Agreements for Nationals and Associated States of MERCOSUR (MERCOSUR 2002a, 2002b), instruments already formalized and internalized in all country members, as they do not have an exclusive or limiting content for these human movements motivated by the impacts of climate change, they would be liable to be applied with intra-bloc administrative and bureaucratic demands, in a simplified way compared to other routes that would require major multilateral and international dealings.